Bioestruturas no solo sob vegetação florestal de Mata Atlântica primária no Sudeste do Brasil - Diogo Filho, Geraldo José; Queiroz Neto, José Pereira de (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2020)
Pedologists generally pay less attention to bioturbation than other soil-forming processes since morphological descriptions and/or soil analytical methods often exclude the characterization of biogenic structures. For example, bioaggregates are not even considered in the Brazilian Soil Classification System. Here, we aimed to address this shortcoming by describing and analyzing biogenic features (e.g., channels, pedotubes, and casts) produced by earthworm activity in soils. Annelid structures in Brazilian Atlantic rain forest soils were collected, measured, and photographed. The bioaggregates were organized by type (cylindrical, irregular blocks) and class (very small, small, medium, large, and very large). Physical and chemical characterization of these structures was also performed, including analyses of soil texture, organic carbon, and exchangeable bases (Ca2+, Mg2+, K+, P). Some biogenic features were filled with revolved soil (i.e. krotovinas or paleoburrows), while others were not (intact channels). Redoximorphic features were very common on the channel walls and casts, likely because these biogenic pores contribute to soil O2 diffusion and CO2 removal. The casts were found to have a sandy texture and organic carbon contents were three times greater – as also exemplified by their darker color – than the surrounding soil matrix. These factors collectively suggest the efficiency with which certain ecological groups of annelids incorporate organic matter into forest soils. Earthworm casts also contained higher quantities of phosphorus, calcium, and magnesium (exchangeable bases) than the surrounding soil. Earthworms are a fundamental part of soil functioning, contributing to essential processes such as aeration, aggregation, organic matter incorporation, and fertility enhancement. Therefore, earthworms and the biogenic structures they are responsible for can be considered to strongly influence pedogenesis, especially in tropical regions.